Introduction to and Discussion Summary of Chiyuki Kumakura's "History and Narrative in Japanese" - Pfeiffer, K. (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1995)
In the context of the Second International Conference on Humanistic Discourse, this text introduces Chiyuki Kumakura's "History and Narrative in Japanese" and reports on the central concerns that emerged in its discussion.